(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
At present, the most vulnerable part of nature and society has become the process of climate change at the present stage. The article considers the problems of climate change in the Central Asian region in the context of air pollution. An analysis of the causes of climate change in the territories of the Central Asian republics and its negative consequences in the modern world is given. The article also considers the factors influencing the process of climate change.